Pheochromocytoma and pregnancy - G. R. Gazizova; F. V. Valeeva; S. R. Karimullina (Медицинский вестник Юга России, 2022)
A clinical case of a pregnant patient with gestational arterial hypertension resulting from pheochromocytoma is presented. Th e article presents an algorithm for diff erential search for the cause of gestational arterial hypertension, clinical and laboratory data and therapeutic measures provided to the patient, on the basis of which endocrinologists together with obstetricians and gynecologists can determine the tactics of pregnancy and delivery of women with hormone-active adrenal tumors.